Venticinque anni dopo. Interviste e scritti di Massimo Fagioli su “Lotta Continua”. 1979-1981 - Fagioli, Massimo; Fagioli, Francesca (Il sogno della farfalla, 2005)
The main focus of attention and research of these texts is the Collective Analysis, a group of therapy which has been conducted by Fagioli since 1975 with thousands of participants. This series of articles represents one of the most significant moments of an on-going dialogue between the group and the Italian left stimulated by the political contents of a form of psychotherapy which is both free and intent on transforming people. The articles gathered over 25 years reveal a mixture of interest, aloofness and hostility towards both Fagioli and his work; the introduction highlights the remarkable transformation which has taken place in respect to Fagioli and the Collective Analysis, in light of recent positive feedback received from some left-wing political leaders.